Effect of different rotary instrumentation techniques and thermoplastic filling on apical sealing Efeito de diferentes técnicas de instrumentação rotatória e obturação termoplástica no selamento apical - Mario Roberto Leonardo; Devanir de Araújo Cervi; Juliane Maria Guerreiro Tanomaru; Léa Assed Bezerra da Silva (University of São Paulo, 2004)
The aim of this study was to evaluate apical sealing after root canal treatment using two different rotary instrumentation techniques and two thermoplastic root canal filling techniques. The study was performed in 115 human extracted mandibular premolars. After coronary access the apical foramen was opened with a # 15 K file 1 mm beyond the apex. Cleaning and shaping was subsequently carried out at the working length, 1 mm from the apex, with ProFile .04/.06 system (Dentsply/Maillefer), Quantec (Analytic Endodontics/Kerr) or by the step-back technique with 1% sodium hypochlorite solution as irrigating solution. The root canals were filled with Thermafil (Dentsply/Maillefer) or Microseal (Analytic Endodontics/Kerr) or by lateral condensation technique using AH Plus sealer (epoxy type). The teeth were immersed in 2% methylene blue under vacuum. Then, they were longitudinally sectioned. The results showed that the association of Profile and Thermafil Plus provide the best results (p<0.05). In conclusion, the association of different rotary instrumentation techniques and different filling systems influenced the apical sealing. O objetivo deste estudo foi avaliar o selamento apical após obturação de canal radicular usando duas diferentes técnicas de instrumentação rotatória e duas técnicas termoplásticas de obturação de canal radicular. O estudo foi realizado em 115 pré-molares extraídos de humanos. Após abertura coronária, o forame apical foi dilatado com lima tipo K 15, 1 mm além do ápice. Em seguida, o preparo biomecânico foi conduzido no comprimento de trabalho, 1 mm aquém do ápice, utilizando o Sistema ProFile 0,04/0,06 (Dentsply/Maillefer), Quantec (Analytic Endodontics/Kerr) ou técnica escalonada com hipoclorito de sódio como solução irrigadora. Os canais radiculares foram obturados com Thermafil (Dentsply/Maillefer) ou Microseal (Analytic Endodontics/Kerr) ou condensação lateral ativa usando o cimento AH Plus. Os dentes foram imersos em solução de azul de metileno a 2% em ambiente de vácuo. Depois, eles foram seccionados longitudinalmente. Os resultados demonstraram que a associação do Profile e Thermafil promoveu os melhores resultados (p<0.05). Conclui-se que a associação de diferentes sistemas rotatórios de instrumentação e diferentes sistemas de obturação influenciaram no selamento apical.